The Image of Peter the Great in Russian History and Thought. - Riasanovsky, Nicholas V. (Oxford University Press, 1992)
The image of Peter the Great, Tsar of Russia from 1689 to 1725, has been a central theme of Russian history, art and literature. This study draws on Russian historical accounts, folklore and the arts to demonstrate how the image of Peter has reflected the changing cultural values of Russian people.